2022
DOI: 10.1021/acs.inorgchem.2c02737
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytically Stable and Cytotoxic [ONON]2Ti(IV)-Type Octahedral Complexes

Abstract: A new family of titanium(IV) complexes based on [ONON] diaminobis(phenolato) ligands with Me, Br, Cl, and F ortho substitutions was synthesized and characterized. X-ray structures of three derivatives revealed homoleptic L 2 Ti-type compounds that exhibit an octahedral geometry without binding of the dangling amine unit. DFT calculations demonstrated that the preference of an L 2 Ti complex is not driven by solvent or ligand substitutions but rather by entropic effects. Except for the fluorinated derivative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Further, the hydrolytic stability of 1 – 4 was evaluated via time-dependent 1 H NMR spectroscopy by adding 10% D 2 O to the complexes in DMSO- d 6 . This study reflects probable knowledge about the relative stability of compounds in aqueous media with respect to time. , From the previous discussion, it was observed that 1 undergoes hydrolysis, whereas 2 – 4 remain stable under the investigation time period. Thus, considering the behavior of complexes, the 1 H NMR spectrum of 1 was collected every 15 min up to 17 h (Figure ), whereas for 2 – 4 , the spectra were collected every 1–2 h interval (Figure S18), and the peak intensity of selected signals was measured to get insights into the hydrolysis process of the complexes.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, the hydrolytic stability of 1 – 4 was evaluated via time-dependent 1 H NMR spectroscopy by adding 10% D 2 O to the complexes in DMSO- d 6 . This study reflects probable knowledge about the relative stability of compounds in aqueous media with respect to time. , From the previous discussion, it was observed that 1 undergoes hydrolysis, whereas 2 – 4 remain stable under the investigation time period. Thus, considering the behavior of complexes, the 1 H NMR spectrum of 1 was collected every 15 min up to 17 h (Figure ), whereas for 2 – 4 , the spectra were collected every 1–2 h interval (Figure S18), and the peak intensity of selected signals was measured to get insights into the hydrolysis process of the complexes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Finally, in nonhydrolyzed vanadium complexes ( 2 – 4 ), ethyl maltol played a major role in easing the transport and absorption in the lipid layer leading to enhancement in the cytotoxicity results. ,,, Thus, complex 2 with maximum hydrolytic stability and hydrophobicity values manifested as the most cytotoxic compound of the series. ,, However, 1 with poor hydrophobicity and hydrolytic stability, which was expected to show the least toxicity, is the second most toxic compound of the series, which may be due to the mixture of active species generated in the incubation media, i.e., the vanadium-hydroxyl, ethyl maltol, and traces of dimeric vanadium, along with the intact species. ,,,,, In addition, the results of biomolecular (CT–DNA/BSA) interaction studies of the complexes have correlated well with the cytotoxicity. 1 and 2 with maximum DNA/BSA binding capacity exhibited maximum cytotoxicity, whereas 3 stands as an exception, though it has high log P ow and t 1/2 results, which showed poor biomolecular interaction resulting in potentially low cytotoxicity. Overall, from these detailed discussions, it can be stated that to be established as a better anticancer agent, a compound should have good hydrolytic stability, effective membrane internalization, and strong biomolecular interactions. ,,,,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations